2009
DOI: 10.1002/ana.21774
|View full text |Cite
|
Sign up to set email alerts
|

Treatment disparities in Parkinson's disease

Abstract: We sought to identify racial disparities in the treatment of Parkinson’s disease (PD). We identified 307 incident PD cases using Pennsylvania State Medicaid claims, and extracted claims for medications, physical therapy, and healthcare visits for the 6 months after diagnosis. After controlling for age, sex, and geography, African-Americans were four times less likely than whites to receive any PD treatment (odds ratio, 0.24; 95% confidence interval, 0.09 – 0.64), especially indicated medications. In a group wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…Nonetheless, cognitive impairment is a stated (but apparently not absolute) contraindication to DBS, and reduced use would be expected in groups with high dementia incidence. Black patients with PD have also been found to have more postural instability on initial presentation, 17 a motor symptom which may not respond well to DBS, and may be viewed as a relative contraindication to DBS. 18 Future prospective studies of these groups are needed to understand how differences in clinical phenotype contribute to patterns of care.…”
Section: Patient Characteristics Standard Medicare Codes Identifiedmentioning
confidence: 99%
“…Nonetheless, cognitive impairment is a stated (but apparently not absolute) contraindication to DBS, and reduced use would be expected in groups with high dementia incidence. Black patients with PD have also been found to have more postural instability on initial presentation, 17 a motor symptom which may not respond well to DBS, and may be viewed as a relative contraindication to DBS. 18 Future prospective studies of these groups are needed to understand how differences in clinical phenotype contribute to patterns of care.…”
Section: Patient Characteristics Standard Medicare Codes Identifiedmentioning
confidence: 99%
“…A study in 2006 estimated that the 5-year risk of L-dopa induced dyskinesias was 50% in patients with disease onset between 50 -59 years and 16% in those with onset after 70 years [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several of the studies observed treatment disparities in PD treatment among African-Americans compared to Caucasians [6][7][8]. The lack of treatment for PD can lead to increased morbidity, decreased quality of life and cause more rapid progression to disability [8].…”
mentioning
confidence: 99%
“…The lack of treatment for PD can lead to increased morbidity, decreased quality of life and cause more rapid progression to disability [8]. After controlling for demographics, age, sex, geography and initial visit with a neurologist, about only one third of African-Americans with PD were started on any therapy, including physical therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation